ISOLASI DAN PENENTUAN AKTIFITAS SPESIFIK KLOROFILASE DARI DAUN MAHONI (Swietenia mahagoni) - Khasanah, Nurlita (Chem Info Journal, 2013)
Enzyme chlorophyllase was isolated and determination specific activity of chlorophyllase from mahoni leaf (Swietenia mahagoni) Several stage of this work including plastid isolation, determination of specific activity chlorophyllase at pH= 7,4 and determination of specific activity of chlorophyllase with pH and incubation time variation. Result showed the highest specific activity in leaf mahogany (Swietenia mahogany) present in acetone with saturation of 80-95%, with value is 13.605 units/mg protein. The influence of pH and incubation time of the higher specific activity of chlorophyllase at pH 8.6 and incubation time of 5 minutes, whereas the smaller specific activity of chlorophyllase at pH 7.0 and incubation time of 45 minutes. The presence of variation pH and incubation time on specific activity of chlorophyllase, showed that variation pH not influence specific activity of chlorophyllase and the longer of incubation time, specific activity of chlorophyllase was decreased.